Market orientation heterogeneity and new joint venture formation announcements: creating value for parent firms. Issue 3 (18th June 2020) - Jancenelle, Vivien E.; Wei, Shuqin; Ang, Tyson
Abstract : Purpose: Joint ventures (JVs) are known to create value for their parent firms, in part due to the mutually beneficial sharing of information that occurs at the JV level. Market orientation (MO) is a well-documented strategic orientation that has received little attention in the JV literature, despite considerable research suggesting that MO has a positive effect on performance. This study posits that the MO skills contributed to a new JV by parent firms are likely to play a central role in a shareholder's assessment of the potential for success of a newly announced JV, thereby triggering changes in market value for parent firms. Design/methodology/approach: Computer-Assisted-Text-Analysis (CATA) is used to calculate MO heterogeneity from annual reports, and event-study methodology is used to assess parent firm performance. The authors rely on a US sample of 82 public JV parents involved in 41 new equally-weighted JV formation announcements. Findings: The authors find that heterogeneity on MO's behavioral components (customer orientation, competitor orientation, and coordination) is negatively related to parent performance, while heterogeneity on MO's profitability component is positively related to parent performance. However, the effect of MO's long-term focus heterogeneity on parent performance was not supported. Originality/value: The results suggest that the benefits of information sharing in partnerships may be of a nuanced nature when it comes to MO. Although heterogeneity in profitability inclination created value for parent firms announcing a new JV; heterogeneity in customer, competitor and coordination market orientations did not appear to be rewarded by shareholders.